Awareness and Utilization of Abattoir Safety Measures in Katsina South and Central Senatorial Districts Nigeria - Nathaniel Siji Olutegbe; Oscar T Ikwuakam (Journal of Agricultural Extension, 2017)
The study assessed utilization of abattoir safety measures in Kastina South and Central senatorial districts, Nigeria. Information was obtained from a total of 80 abattoir workers in each district, while frequency counts, percentages and independent sample t-test were used to analyze data. Majority, in the respective districts, were married (70.0% and 68.8%), Muslims (98.8% and 97.5%), certified butchers (83.8% and 77.5%), with 32.5% and 35.0% having quranic education. Level of awareness of abattoir safety measures was high among majority (85.0% and 91.3%). However, the overall level of utilization of these practices was low among majority (57.5% and 56.3%) in the respective districts. The independent sample t-test result showed no significant difference between the two districts in their levels of awareness (t = 0.805, p = 0.422) and utilization (t = 1.390; p = 0.166) of abattoir safety measures. The study concludes that there is hardly conscious attempt by butchers to ensure that all abattoir safety measures are adhered to in spite of high awareness. Government agencies in charge of enforcement of abattoir safety measures should ensure that violators of these regulations are not spared from facing the full wrath of the law so as to serve as deterrent to others.